2019
DOI: 10.1002/pi.5896
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis behaviours of nanoparticles with helically decorated ligands

Abstract: In this work, the receptor‐mediated endocytosis of nanoparticles with helically decorated ligands was investigated by performing coarse‐grained molecular dynamics simulations. The results showed that a helical distribution of ligands can generate a unique spinning stage during endocytosis in which the nanoparticle is internalized with precession. This precession behaviour is primarily caused by a lateral torque acting on the nanoparticle. Compared with nanoparticles that present uniformly distributed ligands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…An important aspect in tailoring a liposomal system is the optimization of ligand density on the liposomes surface. Previous studies have shown that cellular uptake is increased with an increase of ligand density on the surface of particles. However, issues such as aggregation and suppressed therapeutic effect may result from increasing ligand density beyond an optimum level …”
Section: Combinatorial Adjuvant Strategiesmentioning
confidence: 99%
“…An important aspect in tailoring a liposomal system is the optimization of ligand density on the liposomes surface. Previous studies have shown that cellular uptake is increased with an increase of ligand density on the surface of particles. However, issues such as aggregation and suppressed therapeutic effect may result from increasing ligand density beyond an optimum level …”
Section: Combinatorial Adjuvant Strategiesmentioning
confidence: 99%